A new pyranoxanthone from the stem bark of Calophyllum inophyllum - Mah, Siau Hui; Ee, Gwendoline Cheng Lian; Rahmani, Mawardi; Yap, Taufiq Yun Hin; Go, Rusea; Teh, Soek Sin (Bentham Science Publishers, 2011)
The stem bark of Calophyllum inophyllum gave one new prenylated dipyranoxanthone inophinone (1), together with two other xanthones, inophyllin A (2) and caloxanthone B (3) and three common triterpenes, friedelin (4), stigmasterol (5) and betulinic acid (6). 1D and 2D NMR spectral data (1H, 13C, DEPT, COSY, HMBC & HMQC) were used to elucidate the structures of these compounds.